2013
DOI: 10.1002/ana.23813
|View full text |Cite
|
Sign up to set email alerts
|

Reduced microglial CX3CR1 expression delays neurofibromatosis‐1 glioma formation

Abstract: While traditional models of carcinogenesis have largely focused on neoplastic cells, converging data have revealed the importance of non-neoplastic stromal cells in influencing tumor growth and progression. Leveraging a genetically-engineered mouse model of NF1-associated optic glioma, we now demonstrate that stromal microglia express the CX3CR1 chemokine receptor, such that reduced CX3CR1 expression decreases optic nerve microglia. Moreover, genetic reduction of Cx3cr1 expression in Nf1 optic glioma mice dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 20 publications
0
78
0
Order By: Relevance
“…More specifically, Ptprd +/− p16 −/− tumors had activated genes involved in up-regulation of several chemokines, all of which promote M2 polarization (23)(24)(25)(26). Macrophages can enhance tumor cell survival by promoting tumor growth, invasion, or immunosuppression (27)(28)(29)(38)(39)(40). In addition, recent work by Pyonteck et al showed that RCAS PDGFB gliomas have tumor-associated macrophages, and that inhibiting their polarization state can significantly improve survival (30).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Ptprd +/− p16 −/− tumors had activated genes involved in up-regulation of several chemokines, all of which promote M2 polarization (23)(24)(25)(26). Macrophages can enhance tumor cell survival by promoting tumor growth, invasion, or immunosuppression (27)(28)(29)(38)(39)(40). In addition, recent work by Pyonteck et al showed that RCAS PDGFB gliomas have tumor-associated macrophages, and that inhibiting their polarization state can significantly improve survival (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no reports yet evaluating these cell types in the DIPG microenvironment, studies have shown that cells expressing microglia/macrophage markers comprise 30–50% of the cells in benign and malignant gliomas [40]. While the role of microglia/macrophages in glioma has been controversial [52], recent studies have demonstrated that pharmacologic and genetic inhibition of microglial/macrophage function reduces tumor growth in experimental rodent glioma models [25,29,37] and the inhibition of colony stimulating factor-1 receptor has been shown to block glioma progression in a transgenic mouse model of proneuronal GBM [39]. Intriguingly, it has been hypothesized that microglia/macrophages in the glioma microenvironment may be malignant cells themselves and, given their amoeboid properties, maybe capable of invading the surrounding parenchyma giving rise to tumor growth and even tumor metastasis [21].…”
Section: Discussionmentioning
confidence: 99%
“…In studies of NF1-associated low grade gliomas, David Gutmann (Washington University) presented evidence that human tumors are monoclonal and have no other mutations other than loss of NF1 gene expression[Gutmann et al, 2013]. However, in a genetically-engineered mouse optic glioma model, loss of Nf1 gene expression in glial cells alone is not sufficient to drive tumorigenesis but requires signals from Nf1 +/- microglia in the surrounding microenvironment [Pong et al, 2013]. …”
Section: Neurofibromatosismentioning
confidence: 99%